Implementation of Inquiry Learning Strategy in Islamic Religious Education Learning - Vina Mellyana; Kasja Eki Waluyo; Tajudin Nur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The ability to think is an important aspect in individuals that can generate extraordinary ideas or suggestions. Students need to be trained in thinking skills to enhance their intelligence. Therefore, teachers have knowledge of how to implement strategies or well-planned plans according to these goals to effectively develop thinking abilities. Thus, inquiry-based learning strategies are chosen as the most appropriate teaching method by teachers to enhance students' intellectual skills, as inquiry-based learning emphasizes critical and analytical thinking so that students can seek and find their own answers to the problems they face. In the subject of Islamic Education, research strategies are considered suitable for enhancing thinking abilities. This aims to develop understanding and increase students' intellectual knowledge of materials related to Islamic education.